Relevance of market information system to environment protection - Awasthi, Bishnu D. (Journal of Agriculture and Environment, 2007)
Market information is an important facilitating function in a marketing system. It facilitates marketing decisions, regulates the competitive market processes and facilitates marketing mechanisms. To increase consumption, it is necessary to develop marketing channels. After production, marketing is the most important function, which consists of assembling, processing and distribution of marketable surplus. An efficient marketing information system can manage, for timely delivery of product, reduce marketing costs and increase production and productivity and make the market yard healthy and hygienic. The existing practices of vegetable marketing system consists only the collection of selling price of different vegetables and fruits, volume of arrival and source of origin. Fruits and vegetables are bulky and perishable by nature and need immediate disposal in the market having with clean and proper packaging. If it is not properly done, it generates wastes in the market and pollute the locality. Efficient vegetable market information system can minimize the waste induced problems in the vegetable markets. Environmental policies are influenced by economic, social, and political forces. To ensure that the execution of these policies protects human health and ecosystems effectively and efficiently, scientific and technical information needs to be an integral consideration from the earliest stages of policy making. The Journal of AGRICULTURE AND ENVIRONMENT Vol. 8, 2007, pp. 46-54